2018
DOI: 10.30699/fdisj.01.1.1
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Phonological Processing and Sentence Comprehension of Normal Hearing Children and Those with Cochlear Implant Experience

Abstract: Background and Objective: The purpose of the present study is to investigate the phonological processing and sentence comprehension in children with CIs and compare them with normal hearing (NH) children. It is also an attempt to study the relation between phonological processing and sentence comprehension in children with CIs. Methods: Twenty children with CIs and twenty NH children between the ages 4 to 6 years were evaluated with the Non-Word Repetition (NWR) task ; Persian Syntax Comprehension Test (PSCT);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…This study showed also that children with CI did not perform as well as normal children in the subtest of sentence comprehension which was in line with other studies that were implemented in this respect [17,18]. Our results indicated that children with CI have difficulties in sentence comprehension which may be due to deprivation of phonemic The poor results of the word and sentence repetition subtest in children with CI under this study could reflect the insufficient underlying mechanisms of the repetition task which includes access and integration of word meanings, and syntactic processing.…”
Section: Discussionsupporting
confidence: 91%
“…This study showed also that children with CI did not perform as well as normal children in the subtest of sentence comprehension which was in line with other studies that were implemented in this respect [17,18]. Our results indicated that children with CI have difficulties in sentence comprehension which may be due to deprivation of phonemic The poor results of the word and sentence repetition subtest in children with CI under this study could reflect the insufficient underlying mechanisms of the repetition task which includes access and integration of word meanings, and syntactic processing.…”
Section: Discussionsupporting
confidence: 91%
“…Another study in this area indicates that the understanding and expression "passive verb" in CI children is considerably weaker than NH children (31). The results of the study of sentence comprehension skills suggest that children with CI have phonological processing and sentence comprehension impairments, but by improving the experience in sound processing, the sentence comprehension improves (40). A study for the morpho-syntactic skills of these children showed that children are able to express simple structure, but in using complex structures, they…”
Section: Resultsmentioning
confidence: 98%
“…Four articles focused on phonology (phonology awareness skills) (29,34,35,38). Another four articles concentrated on grammatical skills (understanding and expressing passive verbs and MLU (mean length of utterance) indices, morpho-syntactic abilities and sentence comprehension) as well as some semantic skills (NDW (number of different words)/NTW (number of total words) indices and TTR (Type-Token Ratio)) (31,36,40,42). One article reviewed spoken and written narrative abilities (41) and two studies check out reading skills (33,39).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation